SBSC and Digital Capabilities: The Key to Sustainable Performance of MSMEs (A Systematic Literature Review) - Asri Usman; Mediaty; Neysa A. Siagian; Muh. Adnan. A; Mauizhatul Hasanah Muis (Nomico, 2026)
This study aims to map the current literature landscape, identify scientific consensus, and identify theoretical and methodological gaps in the implementation of SBSC and digital technology in MSMEs. This study applies the Systematic Literature Review (SLR) method based on the PRISMA protocol. Secondary data were sourced from the Scopus database using a specific query with inclusion criteria: scientific journal articles, open access, in English, and published between 2020 and 2026. Based on strict screening, nine primary studies were selected for in-depth analysis. The findings demonstrate a consensus that the BSC/SBSC framework is highly adaptive for MSMEs to synergize non-financial aspects with long-term strategies. Information technology (IT) capabilities, CEO digital leadership, and the integration of Artificial Intelligence (AI) have been empirically proven to improve operational efficiency and organizational knowledge absorptive capacity. However, formal sustainability reporting (such as the GRI standards) is often considered too complex and expensive for micro-scale businesses. A research gap was detected due to the dominance of cross-sectional designs and the minimal exploration of Legitimacy Theory related to non-market social motives. This research responds to this gap by integrating Legitimacy Theory into the SBSC architecture, proposing a simplification of sustainability indicators for micro-administrative capacity, and encouraging a shift in research focus towards a longitudinal approach in the digital service MSME sector.